2022
DOI: 10.1021/acs.est.2c03452
|View full text |Cite
|
Sign up to set email alerts
|

Per- and Polyfluoroalkyl Substances (PFASs) Impair Lipid Metabolism in Rana nigromaculata: A Field Investigation and Laboratory Study

Abstract: Per- and polyfluoroalkyl substances (PFASs) are ubiquitous environmental pollutants, causing environmental threats and public health concerns, but information regarding PFAS hepatotoxicity remains elusive. We investigated the effects of PFASs on lipid metabolism in black-spotted frogs through a combined field and laboratory study. In a fluorochemical industrial area, PFASs seriously accumulate in frog tissues. PFAS levels in frog liver tissues are positively related to the hepatosomatic index along with trigly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…With the insertion of oxygen atoms and the substitution of fluorine by chlorine, the estimated log K OW values of Cl-PFESAs are higher than those of certain detected legacy PFAS . This means that 6:2 Cl-PFESA is more likely to bind to animal tissues and has higher tissue enrichment properties . HFPO-DA was found to exhibited low bioaccumulation potential in the teleost through laboratory experiments.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…With the insertion of oxygen atoms and the substitution of fluorine by chlorine, the estimated log K OW values of Cl-PFESAs are higher than those of certain detected legacy PFAS . This means that 6:2 Cl-PFESA is more likely to bind to animal tissues and has higher tissue enrichment properties . HFPO-DA was found to exhibited low bioaccumulation potential in the teleost through laboratory experiments.…”
Section: Resultsmentioning
confidence: 96%
“…75 This means that 6:2 Cl-PFESA is more likely to bind to animal tissues and has higher tissue enrichment properties. 76 HFPO-DA was found to exhibited low bioaccumulation potential in the teleost through laboratory experiments. Nevertheless, in recent years, HFPO-DA has been detected in wild animals such as carp, bivalves, striped bass, and marine cetaceans.…”
Section: ■ Materials and Methodsmentioning
confidence: 94%
“…Concurrently, in case of liver damage, bile circulation is blocked, ALP activity increases, the utilization of free fatty acids decreases, and the level of free fatty acids in the blood increases, ultimately increasing serum TG levels. Therefore, the variation in serum ALP and TG levels indirectly reflects the degree of liver damage ( 30 ). Our results showed that the serum levels of ALT, AST, ALP, and TG levels were significantly increased in AA-induced mice, indicating serious liver damage ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brain lipid metabolism and the use of different lipids as markers of neurodegenerative diseases have received increasing attention in recent years . Most of the environmental neurotoxic pollutants, such as phthalates, bisphenols, and polyfluoroalkyl substances, have been reported to interfere with lipid metabolism. Therefore, the mechanism by which neurotoxicants function in the whole development period may be through disturbing lipid metabolism and generating abnormal brain lipid levels. During early embryonic zebrafish development, TC comprises the main lipid class in the zebrafish yolk and body .…”
Section: Discussionmentioning
confidence: 99%